Legal essence of the policy of the Soviet state against religion (Journal of actual problems of jurisprudence, 2018)
The author of the article examines the legal essence of the policy of the Soviet state against religion. From the first days of Soviet power atheism campaigned in all sectors of society. The author conducted a historical analysis and conclusions with slelat soveremennyy period.Key words: Soviet state, the right, atheism, religion, history, politics.